Unlocking Public Sector Creativity: The Accelerating Role of Work Engagement in the Nexus of Grit and Servant Leadership - Naomi Valentina Simanjuntak; Aryana Satrya (Eduvest - Journal of Universal Studies, 2026)
This study investigates the influence of grit and servant leadership on employee creativity among civil servants at the Ministry of Transportation, with work engagement serving as a mediating variable. Employee creativity is essential for organizational adaptation and maintaining competitive advantage. Grit, defined as perseverance and consistency, is conceptualized as a personal resource, while servant leadership, characterized by serving followers, represents a job resource. Work engagement, encompassing vigor, dedication, and absorption, functions as the central psychological mediator. The study aims to understand how these factors interact and contribute to enhancing employee creativity in the public sector. The quantitative analysis utilized 648 valid responses from civil servants and employed covariance-based structural equation modeling (CB-SEM). The results indicate that all direct relationships are significantly positive. Both grit and servant leadership exert significant positive effects on work engagement and employee creativity. Additionally, work engagement substantially enhances employee creativity. Importantly, Work Engagement is identified as a significant partial mediator of the effects of both grit and servant leadership on employee creativity. These findings demonstrate that grit and servant leadership jointly promote employee creativity, primarily through increased work engagement. Therefore, organizations are encouraged to foster employee perseverance and strengthen service-oriented leadership to enhance engagement and maximize creativity.